YOUTH SPORTING ACTIVITY SEEN THROUGH COMPETITIONS OF SCHOOL SPORTING ASSOCIATIONS IN THE POŽEGA-SLAVONIA COUNTY (CROATIA) (Fiep Bulletin - online, 2014)
In the school year of 1999/2000, sport professionals in Požega-Slavonia County initiated a project of gathering and systematization of data from the County competitions of school sporting associations. The aim was to edit yearbooks and to point out those who take the credit for the achievements in the domain of school sport. The analysis of these sources showed that the response to the competitions and the rate of occurrence goes in favour of the male population, although the representation of female population in the County high-schools is bigger. The most represented sports among male students are five-a-side soccer (94%), table tennis (94%) and cross-country running (83%), and among female students volleyball (89%), table tennis (79%) and cross-country running (68%). However, the participation of high-school students in the competitions is decreasing over the last decade, in spite of the increasing number of high-schools and their attendants as well as the increasing number of sports and possible competitors. At this point it amounts 10% of the male population and 7% of the female population. Considering the statistic indicators and poor infrastructural conditions in that community regarding sports, several questions appear. The most significant are real possibility of developing the habit of doing sports with young people in schools of Požega-Slavonia County, the competition purposefulness of their school sporting associations, and present motivation of its most important participators – students and teachers. In order to stop the negative trend, the common effort of the experts and civil authorities is needed as well as the initiatives which would stimulate the change of existing attitude of youth towards school sports activities.
Keywords: Croatian school sport; youth sporting competition; high-school sporting associations